Performance of a massive parallel sequencing microhaplotypes assay on degraded DNA. Issue 1 (December 2019) - Turchi, Chiara; Melchionda, Filomena; Pesaresi, Mauro; Fattorini, Paolo; Tagliabracci, Adriano
Abstract: Massively parallel sequencing (MPS) has allowed to analyze a new type of forensic genetic marker, known as microhaplotypes (MHs). MHs appear to be useful for identification purposes, reconstruction of family relationships, ancestry prediction and DNA mixtures deconvolution. Moreover, MHs are potentially suitable for the analysis of degraded DNA samples. We designed a new panel of 29 MHs for MPS assay, with amplicons sizes below 180 bp and we investigated its effectiveness with low amounts of degraded samples. We genotyped a set of real forensic samples together with a set of artificially degraded DNAs. Also, a sensitivity test was assessed by a set of 2800 M DNA dilutions. The Depth of Coverage (DoC) were uniform across all 29 loci, in spite of amplicons size. Genotyping results shown that full profiles can be obtained even in highly degraded samples when the amount of template range from 0.1 to 5.0 ng. Finally, the increase of the number of PCR cycles did not provide an improvement in typing results of low amounts of degraded samples as, in front of higher number of typed loci, higher frequencies of artefacts leading to mistyping are found at 25 cycles.